Instructional Supervision, Teacher Self-Efficacy, and the Strengthening of Teacher Competence on Islamic Education: A Literature Review - Nurani; Desmawati; Evi Gusliana; Nirva Diana; Agus Pahrudin (ISTAWA, 2025)
This study examines the role of instructional supervision in strengthening teacher competence, with a specific focus on the mediating influence of teacher self-efficacy. Despite the recognized importance of supervision in educational improvement, existing literature remains fragmented regarding how supervisory practices, teacher confidence, and competence are interconnected. A structured literature review was conducted, systematically searching peer-reviewed articles from major databases including Scopus, Web of Science, ERIC, and ScienceDirect, using keywords such as “instructional supervision,” “teacher competence,” and “teacher self-efficacy.” Studies published in English between 2000 and 2024 that addressed supervision in school contexts and reported theoretical or empirical findings on teacher competence were included, while non-peer-reviewed and unrelated studies were excluded. The review synthesized findings from diverse methodological designs using thematic analysis, identifying three key patterns: instructional supervision improves pedagogical practice through structured guidance and feedback, teacher self-efficacy mediates the translation of supervisory input into competence gains, and collaborative and reflective supervision approaches amplify both confidence and performance. The analysis highlights that effective supervision is most impactful when it addresses cognitive, behavioral, and affective dimensions of teacher development, integrating practical support with psychological empowerment. The novelty of this review lies in positioning teacher self-efficacy as a central mechanism linking supervision and competence, offering a more holistic understanding than previously reported in isolated studies. These findings have significant implications for educational policy and practice, suggesting that school leaders and supervisors should implement developmental, collaborative, and self-efficacy enhancing supervisory models to optimize teacher professional growth and instructional quality across diverse educational settings.